Nursing interventions for elderly who aged in psychiatric institutions: crossed mapping - Tatiana Gomes da Silva; Rosimere Ferreira Santana; Priscilla Alfradique de Souza (Universidade Federal de Goias, 2016)
Our objective was to cross map terms of Nursing language with the system of Nursing Interventions Classifications, in records of elderly with psychiatric disorders. This is a cross mapping documental study with an intentional sample composed by 30 records of elderly with psychiatric disorders. The data collection and analysis were conducted from July of 2013 to May of 2014, in three steps. We found 392 normalized interventions that resulted in 33 interventions, a mean of 13 per user, represented by 15 behavioral interventions and 10 of basic physiology domain. "Reality orientation", "Socialization enhancement", "Self-care assistance: instrumental activities of daily living" and "Family support" were in 100% of records. We described 16 activities per intervention. Crossed mapping allowed us to build terms corresponding to routine Nursing Interventions for mental health, contributing for assistance practice.